Isolating the Odderon in central production in high energy pA and AA collisions - R. McNulty; V. A. Khoze; A. D. Martin; M. G. Ryskin (European Physical Journal C: Particles and Fields, 2020)
Abstract We study the rapidity dependence of the central exclusive production cross sections of C-even mesons in pA and AA collisions, where A is a heavy ion. We observe qualitatively different behaviour of the contributions arising from $$γ $$ γ -Odderon and Pomeron–Pomeron fusion mechanisms. This can be used to extract the Odderon signal from the events of $$f_2$$ f2 mesons exclusively produced in the forward region. Estimates, obtained using expected values of the Odderon cross section, indicate that the $$γ $$ γ -Odderon contribution may exceed by a few times the Pomeron-induced background in Pb–Pb collisions. Moreover, the Odderon effect can be clearly seen in terms of the asymmetry in pA and AA collisions with the beam and target reversed. It is particularly interesting to note that the asymmetry for $$γ $$ γ -Odderon fusion reaches its maximum value close to 1 in the forward direction, whereas the asymmetry for the Pomeron–Pomeron fusion contribution is small. The role of additional interactions of the $$f_2$$ f2 meson with nucleons in the heavy ion, and also the contributions from secondary Reggeons, are estimated. The photon–Odderon contribution has a large normalisation uncertainty but the enhanced cross-section in the forward region combined with a large asymmetry increases the chance of experimentally detecting the Odderon.